Community Extension Programs in a Small Suburban Community: Its Impact and Basis for Institutional Sustainability and Support - Asio, John Mark; Sardina, Dante; Olaguir, Judy Ann; Obispo, Kristoffer Paul; Macaraeg, Edmar Kent (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
In order to assess the value and effects of an implemented institutional extension program, it needs to be evaluated after some time. This study aims to investigate the level of program outputs and impacts of programs in an adopted community of a local college. It also attempts to discover the relationship between the level of program outputs and the impacts of the programs economically and socially. The investigators used a descriptive-correlation research design among conveniently selected respondents in a small suburban community for the survey. This study also adapted and modified an instrument and used SPSS 23 for the statistical calculation of the study. The investigation revealed that all of the community extension program outputs by the institution got